Landasan Dan Problematika Implementasi Kurikulum Pendidikan Agama Islam Di Era Kontemporer: Studi Systematic Literature Review - Habib Ahmadi; Akhmad Syahri; Musta’in Musta’in (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The Islamic Religious Education (IRE) curriculum plays a strategic role in shaping students’ character in the contemporary era. This study aims to examine the concepts and foundations of IRE curriculum development and to analyze the challenges of its implementation. A qualitative method was employed using a Systematic Literature Review (SLR) approach, drawing on sources from DOAJ, Scopus, and Google Scholar spanning the years 2019–2026. The findings indicate that the PAI curriculum possesses a strong conceptual foundation, encompassing the integration of the tauhid paradigm, modern curriculum theory, and psychological, sociological, and legal approaches. However, implementation in the field still faces challenges such as an overemphasis on cognitive aspects, limited digital literacy among teachers, and a gap between instructional design and actual teaching practices. Therefore, it is necessary to strengthen integrative and contextual implementation strategies so that the PAI curriculum can shape character and internalize Islamic values holistically.